Assessment of the relationship between self-reported cognitive distortions and adult ADHD, anxiety, depression, and hopelessness. (30th April 2016) - Strohmeier, Craig W.; Rosenfield, Brad; DiTomasso, Robert A.; Ramsay, J. Russell
Abstract: The current chart review study examined the relationship between self-reported cognitive distortions, attention-deficit/hyperactivity disorder (ADHD) symptoms, and co-occurring symptoms of depression and anxiety in a clinical sample of adults diagnosed with ADHD. Thirty subjects completed inventories measuring cognitive distortions, ADHD, anxiety, depression, and hopelessness as part of the standard diagnostic evaluation protocol used in a university-based outpatient clinic specializing in adult ADHD. A series of correlational analyses were conducted to assess the relationship between self-reported cognitive distortions, ADHD, anxiety, depression, and hopelessness. Results indicated a significant, positive correlation between self-reported cognitive distortions and ADHD. Responses to individual items on the measure of cognitive distortions were tabulated to identify the prevalence of specific cognitive distortion categories, with Perfectionism emerging as the most frequently endorsed. Further clinical implications of these findings are discussed. Highlights: Limited empirical research addresses the role of cognitive distortions in the treatment of adult ADHD. A significant positive relationship was identified between cognitive distortions and ADHD in the clinical sample. The most commonly endorsed cognitive distortion category was Perfectionism.